Confict management in multiethnic communities: a case study in Southeast Sulawesi, Indonesia - Hos, Jamaluddin; Kusujiarti, Siti; Jumintono, Jumintono; Ambo Upe, Ambo Upe; Muhammad Arsyad, Muhammad Arsyad; Hasniah, Hasniah; Firdaus Yuni Dharta, Firdaus Yuni Dharta; Jemma Natanson, Jemma Natanson (Springer, 2021)
This study aims to identify physical confict management and avoidance between ethnic groups in transmigration settlements. Using a qualitative approach with data collection techniques comprised of observation and in-depth interviews, this research uses interpretive understanding for analyzing the data. Both macro-level and micro-level theories are applied in this research to analyze the interconnections of structure and agency. The fundamental question to be answered in this study is what causes conficts between ethnic groups in transmigration settlement sites and how ethnic group citizens manage conficts so that they do not become open conficts and remain coexistent. Results show that the sources of confict include the legal uncertainty of land ownership and the lack of social platforms for diferent ethnic groups to interact and discuss the problems. Social disparities between ethnic groups and diferences in values and norms also contribute to the confict. However, there was a potential for cooperation between ethnic groups. The diferent ethnic groups tend to restrain themselves and prevent violent confict. The ethnic communities managed the confict by ignoring disputes and making compromises to avoid open disagreements. These compromises involved lowering the demands and expectations of the object of confict; the strategy manages the disputes and helps to reduce open disagreements and support multiethnic communities. In order for the ethnic groups involved in the confict to negotiate and compromise, the availability of social space plays a pivotal role.